Garnet (Almandine-Spessartine) Growth Zoning and Its Application to Constrain Metamorphic History in Dehsalm Complex, Iran (Journal of Sciences, Islamic Republic of Iran)
Dehsalm Metamorphic Complex located in east of Iran consists of regionally metamorphosed rocks intruded by three phases of granitic masses. Synkinematic porphyroblasts of garnet from staurolite-garnet schist present well preserved growth zoning. Electron microprobe analysis of selected garnets was carried out to interpret the origin and pattern of zoning in amphibolite facies garnets and its implication on tectonic history of the Dehsalm Metamorphic Complex. Qualitative and quantitative X-ray maps and rim-to-core profiles for Mn, Mg, and Fe reveal concentric zoning with a well-preserved rim in garnet grains. Gradual decrease in Mn and increase in Fe and Mg from the core to the rim of the garnet porphyroblasts are indicative of continuous growth zoning and absence of retrograde diffusion in garnet. Distributions of Mg, Fe and Mn are concentric in garnet grains, while X-ray map for Ca shows non concentric zoning with spherical and fan type distribution from core to rim. Concentration of Ca is not controlled by cracks and it more likely associated with the regions of crystal weakness. Field observation and absence of zoning in contemporaneous staurolite next to zoned garnet suggest that prograde metamorphism occurred at a widely spaced isograds. The presence of fine concentric growth zoning in garnet porphyroblasts indicates that staurolite-garnet schist was formed under amphibolite facies condition and prior to their homogenization in higher amphibolite facies. The well-preserved garnet growth zoning is a sign that staurolite-garnet schists were rapidly cooled and later metamorphic phases had no effect on regional metamorphic schists in south west of the region.